The Lived Experiences of Fibromyalgia in Taiwanese Women - Whei-Mei, Shih; Lee-Ing, Tsao; Hsiu-Chin, Hsu; Pin-Ru, Hsiao (European Scientific Journal, ESJ, 2018)
Fibromyalgia is characterized by chronic widespread musculoskeletal pain and associated symptoms. It affects people physically, mentally, and socially. The aim of this study was to explore the life experience of women with fibromyalgia in order to gain knowledge which can contribute to increased quality of healthcare. In-depth interviews were used to collect information from nineteen Taiwanese women who were diagnosed with fibromyalgia. Data were analyzed using the content analysis approach. Data analysis revealed four categories: life torture by physical suffering, torment of the mind, treatment seeking, and facing an incurable and unknown illness alone. Each category was described in terms of its properties and subcategories. This article provides information to fibromyalgia patients who suffer from severe chronic pain and related discomforts. Recommendations focus on helping women with fibromyalgia achieve or maintain integrity especially in the conservative oriental people. It is beneficial for both health care professionals and patients.